Production Suspension, Corporate Governance, and Firm Value. Issue 10 (9th August 2022) - Kwon, Yonghyun; Han, Seung Hun; Koh, Young Woo
ABSTRACT: This study investigates the effects of planned and unplanned production suspension on firm value. We find that the increased business risk caused by the production suspension negatively affects firm value. Additionally, good corporate governance alleviates the negative effect of planned suspensions, while only firm-specific factors affect unplanned suspensions. Moreover, among firms facing unplanned suspensions, those with strong governance recover faster than firms with weak governance because the former have stable managerial structures. Finally, business group-affiliated firms cope with planned production suspensions well, whereas they are more vulnerable to unplanned suspensions. The result suggests that the group-level supplier-demander relationships have potential business risk owing to low flexibility in unexpected business situations.